2020
DOI: 10.18865/ed.30.s1.137
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Precision Health Among Racial/Ethnic Minority Communities and the Physicians That Serve Them

Abstract: Background: In order for precision health to address health disparities, engagement of diverse racial/ethnic minority communi­ties and the physicians that serve them is critical.Methods: A community-based participatory research approach with mixed methods was employed to gain a deeper understanding of precision health research and practice among American Indian, African American, Latino, Chinese, and Vietnamese groups and physicians that serve these communi­ties. A survey assessed demographics and opinions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“… 26 , 27 Addressing these and other health inequities in genetic medicine requires that we consider how best to make the potential benefits of precision medicine available to under-resourced communities. 11 , 28 , 29 This sentiment was evident in our interactions with PCPs, all of whom expressed a strong interest in advancing community-based health by promoting genomic research, despite limited evidence of clinical utility in comparable settings and full awareness of the many challenges associated with the clinical management of patients who received a medically actionable result. A consistent sentiment among PCPs was enthusiasm for this research in genomic screening to learn more and consider how precision medicine might benefit their patients in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 26 , 27 Addressing these and other health inequities in genetic medicine requires that we consider how best to make the potential benefits of precision medicine available to under-resourced communities. 11 , 28 , 29 This sentiment was evident in our interactions with PCPs, all of whom expressed a strong interest in advancing community-based health by promoting genomic research, despite limited evidence of clinical utility in comparable settings and full awareness of the many challenges associated with the clinical management of patients who received a medically actionable result. A consistent sentiment among PCPs was enthusiasm for this research in genomic screening to learn more and consider how precision medicine might benefit their patients in the future.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 10 Additionally, patients from lower-resource communities, and the physicians who care for them, are concerned about the affordability of genomic medicine and its potential to widen existing health disparities. 11 - 13 …”
Section: Introductionmentioning
confidence: 99%
“…Once the participants were more informed about precision health (through the facilitator’s introduction of the topics), they became more receptive and expressed positive attitudes toward participating in precision health research and provided input on how texting could be used to recruit and engage Vietnamese Americans in research. Although there is limited prior research on this topic, there was 1 qualitative study (where the lead author of this paper was a collaborator) that had also employed focus groups among American Indian, African American, Latino, Chinese, and Vietnamese groups and found similar findings (ie, limited prior knowledge about precision health) [ 19 ]. Moreover, the same study reported that all Latino, Chinese, Vietnamese, and some African American participants had positive attitudes toward precision health [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there is limited prior research on this topic, there was 1 qualitative study (where the lead author of this paper was a collaborator) that had also employed focus groups among American Indian, African American, Latino, Chinese, and Vietnamese groups and found similar findings (ie, limited prior knowledge about precision health) [ 19 ]. Moreover, the same study reported that all Latino, Chinese, Vietnamese, and some African American participants had positive attitudes toward precision health [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation